2022
DOI: 10.5194/os-18-269-2022
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning and beach cleanup data to explain litter quantities along the Dutch North Sea coast

Abstract: Abstract. Coastlines potentially harbor a large part of litter entering the oceans, such as plastic waste. The relative importance of the physical processes that influence the beaching of litter is still relatively unknown. Here, we investigate the beaching of litter by analyzing a data set of litter gathered along the Dutch North Sea coast during extensive beach cleanup efforts between the years 2014 and 2019. This data set is unique in the sense that data are gathered consistently over various years by many … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The second method has been designed via a combination of previous data sets and models, hereafter called the mismanagement model. It is based on as much observational plastic litter data as possible that are applicable to our analysis (namely litter on Dutch beaches and riverbanks, following Kaandorp et al, 2022 ; van Emmerik et al, 2020 , respectively). The ‘destinations’ are therefore measured Dutch littered plastics and inadequately managed plastics abroad ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second method has been designed via a combination of previous data sets and models, hereafter called the mismanagement model. It is based on as much observational plastic litter data as possible that are applicable to our analysis (namely litter on Dutch beaches and riverbanks, following Kaandorp et al, 2022 ; van Emmerik et al, 2020 , respectively). The ‘destinations’ are therefore measured Dutch littered plastics and inadequately managed plastics abroad ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The volunteers weighed the total litter collected and identified the items (wherever possible) and found that the overall plastic fraction of the litter in terms of numbers is 80–90% ( Kaandorp et al, 2022 ). This matches recent findings from Scottish beached OSPAR data ( Smith and Turrell, 2021 ) (88.3% in terms of numbers, 86.6% in terms of weight).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beaching and resuspension of particles on coastlines is modeled following Onink et al Concentrations of beached microplastics are influenced by a wide range of processes, such as winds, coastal morphology, tides, and human usage of the beach. ,,,,,, However, such processes typically act on smaller spatial and temporal scales than those resolved in ocean reanalysis products. As such, particle beaching is implemented as a stochastic process where a particle’s beaching probability p B for time step dt is p B = true{ lefttrue if d D , p B = 1 exp false( prefix− italicdt / λ B false) if d > D , p B = 0 where d is the distance from the particle to the nearest model land cell, D sets the outer limit of the beaching zone within which beaching is possible, and λ B is the beaching time scale in days.…”
Section: Methodsmentioning
confidence: 99%
“…The beaching and resuspension of particles on coastlines is modeled following Onink et al 62 Concentrations of beached microplastics are influenced by a wide range of processes, such as winds, coastal morphology, tides, and human usage of the beach. 9,10,20,32,40,68,72…”
Section: Lagrangian Transportmentioning
confidence: 99%